Neutrophil-to-lymphocyte ratio as a predictor of prognosis in patients with spontaneous intracerebral hemorrhage: a systematic review and meta-analysis - Guo, Lixia; Cao, Xudong; Chang, Luyao; Liu, Huandong (Frontiers in Neurology, 2025)
ObjectiveTo evaluate the predictive value of the neutrophil-to-lymphocyte ratio (NLR) for prognosis spontaneous intracerebral hemorrhage (ICH) patients.MethodsPubMed, EMBASE, Cochrane Library, Web of Science were used for screening literature on NLR predicting ICH prognosis from database up to January 2024. Case–control or cohort studies that provided statistical analysis data on NLR predicting ICH prognosis were included. Data were combined using odds ratio (OR) and standard mean differences (SMD) for categorical variables and continuous variables, respectively. Meta-analysis, subgroup analyses, and sensitivity analyses were performed by Review Manager 5.4 and Stata 15.0.ResultsMeta-analysis of 21 studies with a total of 7,176 patients confirmed that NLR has a significant predictive value for mortality (SMD: 0.80, 95% CI: 0.58–1.02; OR: 1.10, 95% CI: 1.04–1.17) and neurological function outcomes (SMD: 0.66, 95% CI: 0.50–0.81; OR: 1.29, 95% CI: 1.17–1.41). NLR also significantly predicted the occurrence of stroke-associated pneumonia (SAP) (SMD: 0.54, 95% CI: 0.21–0.87). Subgroup analysis suggested that NLR had good predictive value for mortality in ICH patients aged ≥60 years, with hematoma volume > 15 mL, and NLR cut-off >7.5, and for neurological function in ICH patients, Asian patients, and those with NLR cut-off >7.5. The stability of the results was confirmed by sensitivity analysis.ConclusionNLR can significantly predict mortality, neurological function outcomes, and SAP occurrence in ICH patients. NLR cut-off >7.5 has good predictive value for both mortality and neurological function in ICH patients. Considering the limitations of this study, such as small sample size and potential heterogeneity, prospective studies with larger sample sizes are needed to confirm the findings of this article.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024544506.